PERANAN BANTUAN SOSIAL PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEJAHTERAAN MASYARAKAT DESA CIJEDIL KEC. CUGENANG KAB. CIANJUR - Nurhanifa, Fathia Karunia; Ansori, Ansori (Comm-Edu (Community Education Journal), 2024)
This research is motivated by the welfare of the community has not been achieved, so this research was conducted with the aim of analyzing how the role of Program Keluarga Harapan (PKH) on the welfare of the community. The theory used to strengthen this research are 1. Social Welfare Theory, 2. Society Welfare Theory, 3. Society Education Theory.The research approach used a qualitative approach with research instruments in the form of interviews. The number of respondents involved are 35 peoples. The results of this study illustrate that the role of PKH Social Assistance can improve the welfare of KPM in Cijedil Village, Kp. Gunung Lanjung Kec. Cugenang Kab. Cianjur. The conclusion of this study is that Program Keluarga Harapan (PKH) social assistance really helps Keluarga Penerima Manfaat (KPM) in meeting family needs, especially education and health.